2020
DOI: 10.3390/molecules25163619
|View full text |Cite
|
Sign up to set email alerts
|

Naturally-Occurring Alkaloids of Plant Origin as Potential Antimicrobials against Antibiotic-Resistant Infections

Abstract: Antibiotic resistance is now considered a worldwide problem that puts public health at risk. The onset of bacterial strains resistant to conventional antibiotics and the scarcity of new drugs have prompted scientific research to re-evaluate natural products as molecules with high biological and chemical potential. A class of natural compounds of significant importance is represented by alkaloids derived from higher plants. In this review, we have collected data obtained from various research groups on the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 136 publications
0
32
0
1
Order By: Relevance
“…Alkaloid-rich biorational plant extracts from various families, including Amaryllidaceae, Burseraceae, Capparaceae, Mimosaceae, Vitaceae, and Tiliaceae, have remarkably demonstrated antibacterial activity against mycobacteria (M. fortuitum, M. tuberculosis, and M. smegmatis), E. coli, S. aureus, S. Typhimurium, K. pneumonia and P. aeruginosa (Thawabteh et al, 2019;Omar et al, 2021). Alkaloids have shown broad-spectrum antimicrobial activities, and several studies have suggested that these compounds could represent an important role in tackling pathogenesis of a variety of infection agents (Cushnie et al, 2014;Casciaro et al, 2020). Alkaloids are known to target major drug-resistance determinants, especially the powerful EPs.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Alkaloid-rich biorational plant extracts from various families, including Amaryllidaceae, Burseraceae, Capparaceae, Mimosaceae, Vitaceae, and Tiliaceae, have remarkably demonstrated antibacterial activity against mycobacteria (M. fortuitum, M. tuberculosis, and M. smegmatis), E. coli, S. aureus, S. Typhimurium, K. pneumonia and P. aeruginosa (Thawabteh et al, 2019;Omar et al, 2021). Alkaloids have shown broad-spectrum antimicrobial activities, and several studies have suggested that these compounds could represent an important role in tackling pathogenesis of a variety of infection agents (Cushnie et al, 2014;Casciaro et al, 2020). Alkaloids are known to target major drug-resistance determinants, especially the powerful EPs.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Alkaloids had been studied in modern medicine to validate their traditional use due to their pharmacological properties mainly for antibacterial activities but also for antiviral, anticancer, antifungal and antimalarial (Thawabteh et al, 2019;Casciaro et al, 2020). Thus, higher level of alkaloids in this plant's leaves which ranged between 29.12 and 106.44 mg/ml across solvents fraction indicates its significance and application in treatment of broad infectious diseases associated with multidrug-resistant (MDR) cases (Ghirga et al, 2016;Casciaro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids had been studied in modern medicine to validate their traditional use due to their pharmacological properties mainly for antibacterial activities but also for antiviral, anticancer, antifungal and antimalarial (Thawabteh et al, 2019;Casciaro et al, 2020). Thus, higher level of alkaloids in this plant's leaves which ranged between 29.12 and 106.44 mg/ml across solvents fraction indicates its significance and application in treatment of broad infectious diseases associated with multidrug-resistant (MDR) cases (Ghirga et al, 2016;Casciaro et al, 2020). Terpenoids are known to facilitate membrane disruption using lipophilic compounds and they possess a quite number of medicinal properties such as anti-carcinogenic, antimalarial, antihypertensive, insecticidal, antiviral and anti-ulcer which could validates the use of this plant as a potential antimicrobial drug (Saxena et al, 2013;Kabera et al, 2014;Ndongo, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Tetradium ruticarpum (Figure 11) has been tested by Hochfellner and others for their anti‐mycobacterial potency. Both the alkaloids worked on the inhibition of ATP‐dependent MurE ligase of M. tuberculosis , an enzyme involved in the biosynthesis of peptidoglycan constituent of the bacterial cell wall and inhibited at MIC value ranging from 5 to 20 μg mL −1 [57] …”
Section: β‐Carboline Derivatives As Anti‐tb Agentsmentioning
confidence: 99%
“…-dependent MurE ligase of M. tuberculosis, an enzyme involved in the biosynthesis of peptidoglycan constituent of the bacterial cell wall and inhibited at MIC value ranging from 5 to 20 μg mL À 1 [57]. …”
mentioning
confidence: 99%